Inteligencia emocional en el manejo del estrés en estudiantes de enfermería de la universidad regional autónoma de los andes “uniandes” - Sarchi Mallamas, Cristina Alexandra (2025)
Students in the health area, such as nursing, usually face different challenges during their training, which implies undergoing psychological, social and emotional transformations due to the demanding academic load they are subjected to. This situation is intensified when combining the system of care practices and their regular academic activities, which can trigger stress levels that affect their performance and, therefore, their professional training. In this sense, the following research project was developed with the objective of designing an intervention strategy based on emotional intelligence for stress management at the Universidad Regional Autónoma de los Andes “UNIANDES”, Tulcán campus. Using the mixed research modality, and being a non-experimental cross-sectional study. The study population was 200 nursing students enrolled during the period November 2024 - April 2025 at the Universidad Regional Autónoma de los Andes “UNIANDES”, Tulcán, to which after the application of the inclusion and exclusion criteria, a sample of 164 students who meet these criteria was obtained. The results obtained after the application of the questionnaire Systemic Cognitive Inventory for the study of academic stress, second version of 21 items (SISCO-EA), show that the student population is subjected to moderate levels of stress with 54.03%, as well as the data analysis reflects that nursing students live in a demanding academic environment that generates reactions associated with the same. Likewise, the strategies that students try to apply to stressful situations are insufficient or inadequate, which highlights the importance of strengthening emotional intelligence as a tool to manage stress.